Orthorexia in Athletes: A Comprehensive Review of its Causes, Impact on Health, and Prevention Strategies - Kamila Fuczyło; Karolina Stankevič; Anna-Mariia Chernysh; Aleksandra Dusińska; Jakub Waszczyński; Justyna Woźniak; Justyna Weronika Kmieć; Wiktor Biesiada; Ewelina Kopczyńska; Piotr Kulej (Quality in Sport)
Aim: This review aims to explore the prevalence, causes, health impacts, and management strategies for orthorexia nervosa (ON) in athletes, with a focus on the challenges posed by the lack of standardized diagnostic criteria and the demands of sports that emphasize weight control, physique, and performance.